2002
DOI: 10.1021/jp020240w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Diffusion on the Growth of NaCl Particles by Water Vapour Condensation

Abstract: The hygroscopic growth of NaCl particles was investigated both experimentally and theoretically. Straightforward experiments done with a humidity controlled microbalance show that a macroscopic time (hours to days) is required before the final (equilibrium) size is reached. The developed model shows that the droplets are not homogeneous salt solutions and that a finite liquid phase diffusion resistance exists. This is clearly evident from the experimental data also: the initial stage of growth shows a linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that even though diffusion of electrolytes may not be important for cloud droplet formation, it could be important during their deliquescence. Lehtinen et al [2003] examined this problem experimentally and theoretically; they concluded that the water equilibration timescale for NaCl particles may be large (even hours), depending on their dry size.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that even though diffusion of electrolytes may not be important for cloud droplet formation, it could be important during their deliquescence. Lehtinen et al [2003] examined this problem experimentally and theoretically; they concluded that the water equilibration timescale for NaCl particles may be large (even hours), depending on their dry size.…”
Section: Introductionmentioning
confidence: 99%
“…where is the number of ions a salt dissociates into ( NaCl ¼ 2Þ, andm is solution molality. An application of this method for the case of NaCl in water is well described by Mikhailov et al (2004), who also demonstrate that methods to determine U as a function ofm vary and will, therefore, affect the accuracy of the estimation of a w : A third method for determining a w , for the case of a NaCl solution, is to apply a polynomial fit directly to measurements of a w : A number of studies report theoretically derived and measured values of a w relative to salt solution molality, or relative to Y (Chan, Kwok, and Chow 1997;Chirife and Resnik 1984;Cohen, Flagan, and Seinfeld 1987;Robinson and Stokes 1970;Tang 1996;Lehtinen et al 2003). The NaCl a w values published by Robinson and Stokes (R&S, 1970) are considered among the most reliable estimates and they compare closely to values published in other studies (Chan, Kwok, and Chow 1997;Chirife and Resnik 1984;Cohen, Flagan, and Seinfeld 1987;Tang 1996).…”
Section: Water Activitymentioning
confidence: 99%
“…The assumption that the film layer remains near saturation while / < 1:910/ p may not be true for other salts as it will only occur when the rate of dissolution of the salt core is high relative to the water uptake rate of the growing droplet. Increasing the accuracy of the hygroscopic model by incorporating the kinetics associated with the dissolving salt core is a research topic of interest (Bahadur and Russell 2008;Asa-Awuku and Nenes 2007;Lehtinen et al 2003). However, for NaCl, these results suggest that the relatively simple assumption that the salt core readily dissolves, and that the salt ions immediately mix throughout the film layer to consistently form a saturated solution while the core dissolves, is valid.…”
Section: Model Accuracy During the Initial Growth Phasementioning
confidence: 99%